PEMBELAJARAN APRESIASI SENI MUSIK KELAS VII DI SMP N 18 PADANG - Jeni Amriani; Tulus Handra Kadir; Syahrel Syahrel (FBS Universitas Negeri Padang, 2013)
Abstract The aim of research was to analyze and describe the learning process related to the Competence Standard for Art and Music Appreciation in class VII of SMP Negeri 18 Padang. This research was conducted based on the fact that the student’ achievement in learning was still low. It was more than 50% of the students had score which was under the minimum standard score (75). The result of the research revealed that the causes of the students’ low achievement in learning were the unwell-prepared lesson plan and the learning materials which did not meet the learning goals. Kata Kunci: Perencanaan Pembelajaran, Pelaksanaan Pembelajaran, Materi Pembelajaran, Hasil Belajar.